Surveillance of mucorales resistance to azoles in the waste sorting industry: assessment of filtering respiratory protective devices and gloves - Aranha Caetano, Liliana (2020)
Project EXPOsE. Project nº 23222 (02/SAICT/2016). Project Waste FRPD. Project IPL/2018/WasteFRPD_ESTeSL.